2019
DOI: 10.1186/s40902-019-0208-2
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple brain abscesses treated by extraction of the maxillary molars with chronic apical lesion to remove the source of infection

Abstract: Background Brain abscess is a life-threatening condition that occurs due to complications during a neurosurgical procedure, direct cranial trauma, or the presence of local or distal infection. Infection in the oral cavity can also be considered a source of brain abscess. Case presentation A 45-year-old male patient was transported with brain abscess in the subcortical white matter. Navigation-guided abscess aspiration and drainage was performed in the right mid-frontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…However, on the time being, the timing of these diseases indicates the prevalence of lympho-and hematogenous pathways of spread. Moreover, the local blood flow plays a key role in this [5], [14], [15]. In fact, abundant blood supply to the head and neck is characterized by a powerful network of anastomoses, potentially playing a role in the spread of infection [1].…”
Section: Current Understanding Of the Etiology Of Opid In Soft Tissue...mentioning
confidence: 99%
“…However, on the time being, the timing of these diseases indicates the prevalence of lympho-and hematogenous pathways of spread. Moreover, the local blood flow plays a key role in this [5], [14], [15]. In fact, abundant blood supply to the head and neck is characterized by a powerful network of anastomoses, potentially playing a role in the spread of infection [1].…”
Section: Current Understanding Of the Etiology Of Opid In Soft Tissue...mentioning
confidence: 99%
“…Es konnte gezeigt werden, dass die Sanierung der Infektionsquelle einen Einfluss auf die daraus resultierende Hirnabszess-Infektion hat. Es kann dadurch eine gezielte Behandlung der Infektionsquelle ermöglicht und damit ein weiteres Anfeuern der Inflammation im Hirnabszess verhindert werden[59].Ein weiteres Problem bei der Verwendung vom Verfahren der nächsten Generation, die nur einen kleinen Abschnitt der variablen Region der 16S Untereinheit der ribosomalen Einheit sequenzieren, ist die richtige Spezieszuordnung von bestimmten Bakterien, die sich in diesem Bereich nur gering voneinander unterscheiden, sodass nur eine Identifikation auf Genus-Ebene gelingt[60]. Hier wurden jedoch auch bereits Ansätze entwickelt, wie die gesamte 16S DNS sequenziert werden kann, um so eine bessere Zuordnung auf Speziesebene zu ermöglichen[61].Ein Schwerpunkt dieser Arbeit soll auch auf die Verlässlichkeit der Ergebnisse beim Erregernachweis gelegt werden.…”
unclassified
“…[24,25] Jung et al showed that odontogenic infections are a blood-borne cause of brain abscesses, accounting for < 2% of cases. [14,26] Recent dental treatments, such as tooth extraction and caries treatment, as well as poor oral hygiene and diseases, such as diabetes, are known risk factors for developing brain abscesses due to transient bacteremia associated with a decrease in immunity. [14] Clancy et al reported a rare parietal lobe abscess caused by Actinomyces meyeri 7 days after tooth 37 (mandibular left second molar) extraction in a generally healthy 55-year-old female.…”
Section: Pathogenesismentioning
confidence: 99%